IMPACT OF AIRBNB ON PHILIPPINE ACCOMMODATION SECTOR: A QUANTITATIVE APPROACH - Mary Vida L. Tumbali (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The study aimed at scrutinizing the impact of Airbnb on the Philippine hotel accommodation sector with regards to occupancy rates and the number of tourist arrivals. The more extensive point was to make a functional contribution to the current discussions and issues around the sharing accommodation, in particular Airbnb platform, from an ethnically diverse country standpoint. This study used a quantitative explanatory approach, and a secondary data sampling technique was adopted. Statistics from the Philippines were obtained from the DOT library while Airbnb data was purchased from AirDNA last September-November 2019. Secondary data collected were analyzed through SPSS. The study measured the relationship between Airbnb occupancy rates and tourist arrival. Moreover, to test whether Airbnb is directly competing with the lower category of hotel in terms of occupancy rates, the correlational examination was taken into account. Pearson R coefficient was utilized followed by a regression analysis to come up with a model. The findings inferred that it is Airbnb that has most influenced the activity of the tourism industry sector most especially under the accommodation sector and apparently set up to be a threat to the budget traditional providers. The result of the examination required for a business reaction for the traditional providers on the best way to team up with Airbnb to give better accommodation preferences for the increasing number of travelers in the country.